Kualitas Pelayanan Penerbitan Nomor Induk Berusaha Usaha Mikro pada Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kota Pekanbaru - Mariza Mariza; Harapan Tua (Pusat Riset dan Inovasi Nasional, 2025)
Service quality is the level of excellence or specialty of a service that can meet the needs and expectations of the community. Public service is an activity carried out by the government and other institutions to meet the needs of community services in accordance with laws and regulations. This service can be in the form of public goods, public services, and/or administrative services. The purpose of this study was to determine the quality of service in issuing Business Identification Numbers for micro businesses at the Pekanbaru City Investment and One-Stop Integrated Service Office and its supporting and inhibiting factors. This study uses a qualitative approach. Data collection techniques use interviews. Data analysis in this study was carried out using qualitative descriptive. The results of the study explain that the quality of service is already in the good category which is assessed from the transparency in the services provided where there is openness in the service process, services that are in accordance with the rules and there is ease in the service process. The principle of accountability in improving service quality to ensure that each service can be accounted for and provide services in accordance with the conditions that have been set. Community participation in improving services has been carried out well by providing services according to rights and balance. Supporting factors in improving service quality include the ability of employees to serve, the availability of supporting facilities and infrastructure, and the development of a better service system as part of improving services. While inhibiting factors include increased supervision and complicated bureaucracy in efforts to improve services.